Robust assembly of urchin-like NiCo2O4/CNTs architecture as bifunctional electrocatalyst in Zn-Air batteries. Issue 5 (1st April 2020) - Xiao, Xiao; Li, Xinhai; Wang, Jiexi; Yan, Guochun; Wang, Zhixing; Guo, Huajun; Liu, Yong
Abstract: Cost-effective bifunctional electrocatalysts with desirable oxygen catalytic activity to both of ORR and OER are essential to the large-scale commercial application of metal-air batteries. In this work, a robust hydrothermal assembly strategy is presented to fabricate the three-dimensional (3D) urchin-like hybrid material of acid-treated multiwall CNTs (MWCNTs) and needle-like NiCo2 O4 as a cost-effective bifunctional oxygen electrocatalyst. Benefiting from the particular 3D urchin-like mesoporous structure providing rich transport channels for O2 diffusion and electrolyte infiltration and abundant active sites for charge transfer reaction, and the synergistic effect of high electrocatalytically active NiCo2 O4 and high conductive MWCNTs network, the optimized NCO@20%MWCNTs composite exhibits a superior OER and ORR catalytic activity. In its practical application, an ultrahigh initial round-trip efficiency of 79.4% and long-term cycle stability (950 cycles) at 10 mA cm −2 are achieved in Zn-air battery. This simple strategy for construction of the cost-effective unique 3D porous urchin-like structure together with the improved electrochemical catalytic activity provides a great potential for material design in oxygen catalysis and metal-air batteries.